Determinants of Online Purchase Intention of Seasonal Goods in Nigeria: A Conceptual Model and Proposition - Nwakaji, Christopher; Goh, Yen Nee (Journal of Entrepreneurship, Business and Economics, 2021)
In the past few decades, studies in online purchase intention have received a great deal of attention from researchers in developed countries compared to developing countries. Despite this growing interest, there is insufficient research on online purchase intention of seasonal goods from existing literature. Hence, this paper aims to examine the determinants of online purchase intention of seasonal goods in Nigeria. The paper identified perceived economic benefit, perceived transaction security as factors that may influence online purchase intention of seasonal goods. The study proposed a quantitative research design. Hence data will be collected from online shoppers in Nigeria purposively selected based on established criteria. The data collected from the field survey will be analyzed with PLS-SEM. The study being a conceptual paper, proposed the relationship between perceived economic benefit, perceived transaction security and online purchase intention of seasonal goods through the mediating role of perceived value. Future researchers should conduct an empirical study using the conceptual framework of this paper. The limitations identified in this paper will facilitate discussions on the need to deepen the understanding of the determinants of online purchase intention of seasonal goods. The study will contribute to the existing literature by identifying the factor (s) that influence the online purchase of seasonal goods. Research paper Keywords: E-Commerce; Online purchase intention; Seasonal goods; Perceived economic benefit; Perceived transaction security and perceived value Reference to this paper should be made as follows: Nwakaji, C., & Goh, Y. N. (2021). Determinants of Online Purchase Intention of Seasonal Goods in Nigeria: A Conceptual Model and Proposition. Journal of Entrepreneurship, Business and Economics , 9 (2), 218–252.